2023
DOI: 10.1088/1361-6668/acdf8d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on nonuniform current density and shape deformation affecting the magnetic field performance of a saddle-shaped no-insulation HTS cosine–theta dipole magnet

Abstract: In particle accelerators, high magnetic fields are desirable for discovering new particles. Dipole magnets using superconductors have played a key role in creating required field intensity and uniformity. In contrast, high temperature superconductor (HTS) dipole magnets have recently been spotlighted because of their ability to generate higher magnetic fields compared to their low temperature superconductor counterpart. Similar needs have emerged in other fields using magnets, and no-insulation (NI) technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…We therefore begun surveying missing considerations in the material properties that could produce differences in quench voltages between simulation and measurement. In this way, we found that the contact resistance of NI REBCO coils, one of the key simulation parameters in quench analysis, has not been characterized by the magnetic field and mechanical force [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore begun surveying missing considerations in the material properties that could produce differences in quench voltages between simulation and measurement. In this way, we found that the contact resistance of NI REBCO coils, one of the key simulation parameters in quench analysis, has not been characterized by the magnetic field and mechanical force [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%